Making climate governance global: how UN climate summitry comes to matter in a complex climate regime. Issue 4 (4th July 2017) - Lövbrand, Eva; Hjerpe, Mattias; Linnér, Björn-Ola
ABSTRACT: This article examines the role the UNFCCC plays in a polycentric climate regime complex. Through an extended questionnaire survey at the UN Climate Conferences in Warsaw (2013), Lima (2014) and Paris (2015), we study what government delegates and non-state observers see as the main purpose of UN climate summitry and their roles therein. Only a minority of these actors attend UN Climate Conferences to actively influence the outcome of the intergovernmental negotiation process. Instead, most come to these meetings to network, build interpersonal relationships, learn from each other and foster a sense of community across scales of difference. The ability of the UNFCCC to bring together different actors across time and space, to perform multiple policy tasks, has become one of its notable strengths and is an important facilitative practice that holds the polycentric regime complex together.